Fronts and waves of actin polymerization in a bistability-based mechanism of circular dorsal ruffles - Erik Bernitt (Nature Portfolio, 2017)
Circular dorsal ruffles (CDRs) are important for the vesicular uptake of extracellular matter, but the basis of their wave dynamics is not understood. Here, the authors propose and experimentally test a bistable reaction-diffusion system, which they show accounts for the typical CDR expansion and shrinkage and for aberrant formation of pinned waves and spirals.